Peranan PT. Permodalan Ekonomi Rakyat (PER) Dalam Peningkatan Ekonomi Masyarakat Di Provinsi Riau - fahrial; Rini Fatriani; Jenita (Jurnal Economica, 2020)
PT. PER as society wervice institution and PAD source in the economic crisis condition still exist and felt its role. The people economic improvement faces complex problem. The activities in the real sectors grow and will need huge capital. The role of PT. PER will be importanc in improving the society economic. The society economic development and improvent faces complex problem such as : the difficulty in accessing capital, the low of human resoureces quality, the limited technology mastering, the wenk management (financial and marketing), the low quality product and the weak institution and the institution arrangement in developing and empowering the people economic still non optimum. In the problems formulation, the writer discloseded qualitative and quatitative data. The results tried to describe the phenomenon about the PT. PER roles in improving the society economic at Riau Province. The results showed that during four years operation, ther is credit channeling improvement from year to year. PT. Permodalan Ekonomi Rakyat (PER) able to be “agent of development” in the economic recovery, able to distribute economic factors more evenly to people and has big multiplier effect. With PT. PER presence, the micro, small, middle business and cooperative and financial institution of Bank (BPR/S) and micro financial institution (UEK/D-SP), BMT) farmer group and other that formerly difficult to obtained business capital able to access PT. PER.The othe positive impact is PT. PER also contribute in illuminating the society attitude become bank minded.